Effect of Super Retarder on Recycled Water and Concrete Properties of Waste Slurry in Mixing Plant - Jinyue Wang; Yanfeng Zuo; Lixiong Gao; Siqin Liu; Guang Yang (Applied Sciences)
A large amount of waste slurry water will be generated in the production process of concrete mixing plant, due to the complex composition of waste slurry water, if it is not handled in time when stored, serious coagulation will occur, which will accelerate the loss of equipment and reduce the utilization rate. In this paper, a super retarder suitable for waste slurry recycled water from concrete mixing plant was prepared using composite technology. The waste slurry recycled water mixed with super retarding agent was characterized by using microscopic testing means XRD, TG and DTG. The waste slurry recycled water mixed with super retarding agent was used to replace tap water in the production of concrete, and its effect on the workability and mechanical properties of concrete was investigated. It was found that the compounding of Butane 2-phospho-1,2,4-tricarboxylic acid (PBTCA) with Reclaimed water treatment agent (ACS) resulted in a setting time of 64 h for 10% concentration of recycled water, with optimal retarding effect. When PBTCA:ACS was 1:20, mixed at 1.5% of the mass of recycled water, the 1 h slump of concrete had no loss, the loss of extension was 15 mm, the 7 days compressive strength was increased by 3.5 MPa, and the 28 days compressive strength was increased by 3.0 MPa. The microscopic results showed that the use of ACS and PBTCA does not affect the type of cement hydration products, but only affects the the rate of hydration product generation.